Pituitary Glioblastoma: A Case Report - Anvari, Kazem (Iran J Cancer Prev, 2015)
INTRODUCTION: Pituitary adenomas have been the most common sellaturcica tumors. There have been many unusual types of pituitary tumors that might neglect by radiologists and clinicians. One of these tumors would be the malignant glioma. CASE PRESENTATION: A 62-year-old male has complained from sudden frontal headache, nausea, vomiting, decreased vision, blurred vision and double vision. In skull radiographic, there was an expansion of sellaturcica and a lesion with clear border on T1; heterogeneous; iso - to hypotense; size about 3/5 × 2/5 cm with no surrounding edema that it has homogeneously attracted contrast Lesion, that shown a signal hypointensity on T2 with heterogeneous enhancement. In the coronal sections, the tumor expanded to the suprasellar region and optic chiasmatic that has compressed especially on the left side. Partial tumor resection has conducted. The surgery has done by a transsphenoidal approach. The pathologist has diagnosed a glioblastoma. This diagnosis has confirmed using immunohistochemistry technique. CONCLUSIONS: There have been many unusual types of pituitary tumors that might neglect by radiologists and clinicians. One of these tumors would be the malignant glioma.